Modeling Volatility Spillovers between the Variabilities of US Inflation and Output: the UECCC GARCH Model - Christian Conrad; Menelaos Karanasos (University of Heidelberg, Department of Economics, 2008)
This paper employs the unrestricted extended constant conditional correlation GARCH specification proposed in Conrad and Karanasos (2008) to examine the intertemporal relationship between the uncertainties of inflation and output growth in the US. We find that inflation uncertainty effects output variability positively, while output variability has a negative effect on inflation uncertainty.
Keywords: C32; C51; E31; 330; Bivariate GARCH process; negative volatility feedback; inflation uncertainty; output variability; Inflation; Volatilität; Konjunktur; Risiko; Korrelation; ARCH-Modell; Schätzung; USA